Enhanced spin–orbit torque and field-free switching in Au/TMDs/Ni hybrid structures. Issue 7 (26th January 2023) - Luo, Yi; Chen, Qian; Li, Rongxin; Wang, Yipeng; Lv, Weiming; Zhang, Baoshun; Fan, Yaming; Wu, Hao; Zeng, Zhongming
Abstract : This paper explores an effective strategy to enhance the SOT efficiency and achieve field-free magnetization switching, by employing two-dimensional transition metal dichalcogenide (2D TMD) interfaces to conventional magnetic heterostructures. Abstract : Spin–orbit torque (SOT) plays a significant role in spintronic logic and memory devices. However, due to the limited spin Hall angle and SOT symmetry in a heavy-metal–ferromagnet bilayer, further improving SOT efficiency and all-electric magnetization manipulation remain a challenge. Here we report enhanced SOT efficiency and all-electric switching in Au based magnetic structures, by inserting two-dimensional transition metal dichalcogenides (2D TMDs) with large spin–orbit coupling. With the TMD spacer insert, both damping-like and field-like SOTs are improved, and an unconventional out-of-plane damping-like SOT is induced, due to the interface orbital hybridization, modified spin-mixing conductance and orbital current. Moreover, current induced field-free magnetization switching is demonstrated in Au/WTe2 /Ni and Au/MoS2 /Ni devices, and it shows multiple intermediate states and can be efficiently controlled by an electric current. Our results open a path for increasing torques and expand the application of 2D TMDs in spintronic devices for neuromorphic computing.